Enhanced production of a single domain antibody with an engineered stabilizing extra disulfide bond. Issue 1 (December 2015) - Liu, Jinny; Goldman, Ellen; Zabetakis, Dan; Walper, Scott; Turner, Kendrick; Shriver-Lake, Lisa; Anderson, George
Abstract Background Single domain antibodies derived from the variable region of the unique heavy chain antibodies found in camelids yield high affinity and regenerable recognition elements. Adding an additional disulfide bond that bridges framework regions is a proven method to increase their melting temperature, however often at the expense of protein production. To fulfill their full potential it is essential to achieve robust protein production of these stable binding elements. In this work, we tested the hypothesis that decreasing the isoelectric point of single domain antibody extra disulfide bond mutants whose production fell due to the incorporation of the extra disulfide bond would lead to recovery of the protein yield, while maintaining the favorable melting temperature and affinity. Results Introduction of negative charges into a disulfide bond mutant of a single domain antibody specific for the L1 antigen of the vaccinia virus led to approximately 3.5-fold increase of protein production to 14 mg/L, while affinity and melting temperature was maintained. In addition, refolding following heat denaturation improved from 15 to 70 %. It also maintained nearly 100 % of its binding function after heating to 85 °C for an hour at 1 mg/mL. Disappointingly, the replacement of neutral or positively charged amino acids with negatively charged ones to lower the isoelectric point of two anti-toxin single domain antibodies stabilized with a second disulfide bond yielded only slight increases in protein production. Nonetheless, for one of these binders the charge change itself stabilized the structure equivalent to disulfide bond addition, thus providing an alternative route to stabilization which is not accompanied by loss in production. Conclusion The ability to produce high affinity, stable single domain antibodies is critical for their utility. While the addition of a second disulfide bond is a proven method for enhancing stability of single domain antibodies, it frequently comes at the cost of reduced yields. While decreasing the isoelectric point of double disulfide mutants of single domain antibodies may improve protein production, charge addition appears to consistently improve refolding and some charge changes can also improve thermal stability, thus providing a number of benefits making the examination of such mutations worth consideration.